2023
DOI: 10.1186/s43019-023-00197-z
|View full text |Cite
|
Sign up to set email alerts
|

Ramp lesion in anterior cruciate ligament injury: a review of the anatomy, biomechanics, epidemiology, and diagnosis

Bo Seung Bae,
Sunin Yoo,
Sang Hak Lee

Abstract: Ramp lesions, commonly observed in patients with anterior cruciate ligament (ACL) injuries, have been previously defined as longitudinal tears around the meniscocapsular junction. However, the definitions and interpretations of ramp lesions have varied, emphasizing the need to confirm their presence before surgery and the importance of direct visualization using arthroscopy. Recent histological studies have reported new findings on ramp lesions, shedding light on their attachment mechanisms. The anatomical str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…This is a key aspect, since meniscal tears represent one of the most common injuries in orthopaedics, with a mean annual incidence of 60−70 per 100.000 [23], and since patients undergoing ACL reconstruction have been reported to have a meniscus tear incidence from 55% up to nearly 80% [24][25][26][27][28]. Meniscal lesions should therefore be carefully considered when performing ACL reconstruction surgery to restore knee stability [29][30][31][32]. In fact, while meniscectomy can increase the femoro-tibial contact stress and anterior tibial translation in ACL-deficient knees, meniscal repair showed to increase anteromedial knee laxity [8,33].…”
Section: Discussionmentioning
confidence: 99%
“…This is a key aspect, since meniscal tears represent one of the most common injuries in orthopaedics, with a mean annual incidence of 60−70 per 100.000 [23], and since patients undergoing ACL reconstruction have been reported to have a meniscus tear incidence from 55% up to nearly 80% [24][25][26][27][28]. Meniscal lesions should therefore be carefully considered when performing ACL reconstruction surgery to restore knee stability [29][30][31][32]. In fact, while meniscectomy can increase the femoro-tibial contact stress and anterior tibial translation in ACL-deficient knees, meniscal repair showed to increase anteromedial knee laxity [8,33].…”
Section: Discussionmentioning
confidence: 99%
“…Medial meniscus ramp tears are meniscal tears associated with anterior cruciate ligament (ACL) tears and have been reported to be more prevalent when an ACL reconstruction (ACLR) is delayed [1]. Medial meniscus ramp tears have been described as longitudinal tears of the posterior horn of the medial meniscus at the meniscocapsular junction, affecting either the meniscocapsular (superior attachment), meniscotibial (inferior attachment), or both attachments [1,2]. A complete separation of the meniscocapsular junction occurs when both the meniscocapsular and meniscotibial attachments are torn.…”
Section: Introductionmentioning
confidence: 99%
“…Medial meniscus ramp tears have detrimental effects on overall knee stability and if left untreated, can contribute to the early progression of osteoarthritis [9]. Biomechanical studies have reported that concomitant ACL and medial meniscus ramp tears increase anterior tibial translation and internal rotation of the knee compared to an isolated ACL tear state [1,10,11]. Additionally, repairing a ramp tear can restore near native knee biomechanics compared to the unrepaired state [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Integral to knee function, the menisci mitigate the forces transmitted across the knee, reducing the risk of cartilage damage and osteoarthritis [11][12][13][14][15]. The medial meniscus, being C-shaped and firmly attached to the knee's capsule, is particularly vulnerable to injury, underscoring the importance of preserving its integrity for maintaining knee health [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%